The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1007/bf00033386
|View full text |Cite
|
Sign up to set email alerts
|

Cellulase gene expression in ripening avocado fruit: The accumulation of cellulase mRNA and protein as demonstrated by cDNA hybridization and immunodetection

Abstract: A cDNA library was constructed from poly(A)(+)RNA of ripe avocado fruit. Colony hybridization identified a number of ripening specific clones of which one, pAV5, was shown to be specific for cellulase. Hybrid selection with pAV5 provided a message from ripe fruit that on in vitro translation yielded a polypeptide of 53kD, comigrating with purified avocado cellulase on SDS polyacrylamide gel electrophoresis. The translation product was selectively immunoprecipitated by antiserum to purified avocado cellulase. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
75
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 20 publications
3
75
0
Order By: Relevance
“…One class of cell-wall hydrolases, cellulases or EGases (EC 3.2.1.4), has been specifically implicated in a number of developmental processes, including cell expansion (Hayashi and Maclachlan, 1984) and organ abscission (Sexton and Roberts, 1982), as well as ripening-associated fruit softening (Hall, 1964;Hobson, 1968;Christoffersen et al, 1984).…”
mentioning
confidence: 99%
“…One class of cell-wall hydrolases, cellulases or EGases (EC 3.2.1.4), has been specifically implicated in a number of developmental processes, including cell expansion (Hayashi and Maclachlan, 1984) and organ abscission (Sexton and Roberts, 1982), as well as ripening-associated fruit softening (Hall, 1964;Hobson, 1968;Christoffersen et al, 1984).…”
mentioning
confidence: 99%
“…To date, studies of selective gene expression associated with overt avocado ripening have been limited to the climacteric (Christoffersen et al, 1982(Christoffersen et al, , 1984, no attention having been paid to preclimacteric molecular events.…”
mentioning
confidence: 99%
“…In conjunction with the studies of selected clones from our mixed library, we investigated the expression of four ripening-associated genes screened from an early cDNA library (Christoffersen et al, 1984), viz. genes encoding cellulase, PG, P-450, and EFE.…”
mentioning
confidence: 99%
“…Changes in translatable mRNA populations were shown to occur in ripening fruit (Speirs et al, 1984;Christoffersen et al, 1982) and a number of these products were identified, among the first of which were the cell wall hydrolases endo-b-1,4-glucanase (Christoffersen et al, 1984) and polygalacturonase (DellaPenna et al, 1986). In addition, a large number of other ripening-regulated genes have been identified including those that encode ethylene biosynthetic enzymes, lycopene biosynthetic enzymes and proteases.…”
Section: Genetic and Biochemical Determinants Of Fruit Ripeningmentioning
confidence: 99%